TRANSFORMASI ADMINISTRASI PENDIDIKAN MELALUI PUSAT LAYANAN DIGITAL : INOVASI DALAM KONSELING BK DAN BIMBINGAN KARIR - Andi Tanri Bulan; Arismunandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The transformation of educational administration through digital service centers has emerged as a strategic innovation for enhancing the effectiveness of Guidance and Counseling (BK) services and career guidance in the digital era. This article is a theoretical review that examines the paradigm shift from conventional service systems to more responsive, integrated, and data-driven digital platforms. Through an analysis of recent literature, this paper explores the concept of digital educational administration, service innovation models, and the implementation of technology in counseling and career development. The review findings indicate that digital service centers improve accessibility, service speed, intervention personalization, and data-based decision-making quality. Additionally, digitalization enables real-time student monitoring systems, strengthens stakeholder collaboration, and supports administrative automation. However, challenges such as digital literacy, data security, and infrastructure readiness must be addressed throughout the transformation process. This study concludes that digital service center innovation plays a significant role in enhancing educational administration and improving the quality of guidance and counseling as well as career services in modern educational environments.